Predicting dimensions of clinical-functional conditions and cognition in the elderly - Jenifer Nogueira Martins Araujo da Silva; Marinês Tambara Leite; Luana Caroline Gaviraghi; Vanessa Ramos Kirsten; Sandra da Silva Kinalski; Leila Mariza Hildebrandt; Margrid Beuter (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To evaluate the predictive dimensions of clinical-functional conditions and the cognitive capacity of elderly people living at home. Method: Cross-sectional, population-based, analytical, quantitative study was utilized. For data collection, an instrument with sociodemographic and behavioral variables, the Functional Clinical Vulnerability Index; and, to assess cognition, the Mini-Mental State Examination (MMSE) was used. Descriptive analyzes and statistical tests were conducted. Results: 305 elderly subjects, living at home, in urban and rural areas participated in the study. They were classified as robust (71.8%), pre-frail (22%) and frail (6.2%). As for cognition, 24.9% of them had cognitive impairment. It was shown that cognitive impairment predicts the development of functional disability. Conclusion: It is considered that health professionals should both act in order to maintain the functional and cognitive conditions of the robust and pre-frail elderly people and pay attention to the rehabilitation of the disabilities installed in those elderly people who are in a situation of frailty.